PROFESSIONALLY-ORIENTED APPROACH TO TEACHING THE DISCIPLINE "THEORY AND HISTORY OF STATE AND LAW" AT THE LYCEUM OF THE MINISTRY OF INTERNAL AFFAIRS (Eureka Journal of Education & Learning Technologies, 2026)
The article, prepared on the basis of the experience of teaching at the Academic Lyceum of the Ministry of Internal Affairs of the Republic of Uzbekistan, considers the theoretical and applied aspects of the implementation of a professionally-oriented approach in the study of the discipline "Theory and History of State and Law". The need to transform the content of the training course is substantiated, taking into account the variety of areas of future service activities of graduates - investigation, criminal investigation, crime prevention, criminalistics, Methodological ways to ensure the connection of theoretical provisions with the practice of law enforcement in conditions when the discipline is studied in the first year in parallel with constitutional law, and branch legal disciplines begin in the second year. Particular attention is paid to promising areas for the introduction of innovative teaching methods adapted to the specifics of the educational process in the departmental lyceum.
Keywords: Professionally-oriented approach, theory and history of state and law, Lyceum of the Ministry of Internal Affairs, content of training, connection between theory and practice, innovative teaching methods, interdisciplinary connections.